(untitled) (Journal of Hama University, 2020)
The aim of this study is to show the effect of applying the Corporate Governance Index issued by the General Council of Islamic Banks and Financial Institutions and the World Bank on the financial performance of Syria International Islamic Bank through illustrating the effect of this application on the return on equity and the return of assets. Based on the descriptive approach, the study analyzes the bank’s annual reports from 2008 to 2017 in order to calculate the values of the 6 index axes, which are: management board, management committees, internal auditing and external checking, risk governance, Sharia-based governance, disclosure, and transparency. The simple-linear-regression method was also used to examine the effect of applying the above-mentioned index on the financial performance of Syria International Islamic Bank. The study findings show that there is no statistically significant effect of applying the above-mentioned index on the bank’s financial performance, and that is due to the fact that the bank did not reach the full value of the index—36 degrees—in the period studied.